ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI INDEPENDENSI AUDITOR EKSTERNAL MENURUT PERSEPSI BANKIR - Amilin ,; Wiwik Utami; Soliyah Wulandari (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2008)
The objective of this research is to analyze factors that influence external auditor independence on bankers perception. The factors are: (1) audit committee, (2) financial condition of the firm, (3) management advisory services, (4) level of audit firm competition, and (5) tenure of the audit firm. Research design which is used is quasi experiment Experimental design is used because the researcher's objective are to find out banker's perception on various condition of the firm, both in client and audit firm. Treatments are given by different questionair to 32 respondents that has been chosen randomy. Questionair which is used are adopted of Gill (1989). ANOVA (Analysis of Variance) and normality data tests are used to analyse data.The result of this research shows that: Maud& committee and management adidsory services are influence external auditor independence on banker's perception, (2) financial condition of client firm, level of audit firm competition and tenure of the audit firm doesnl influence external auditor independence on banker's perception. Actually, all factors are influence external auditor independence, but audit committee and management advisory services are influence external auditor independence significanty The results of this reaserth are relevance with Indonesia's condition, which is in Indonesia, audit committee are demanded as a part of good corporate governance.Keywords: independence auditor, external auditor, banker's perception